2022
DOI: 10.14740/cr1307
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Resource Utilization for Oral Anticoagulant Reversal Therapies in Non-Valvular Atrial Fibrillation/Venous Thromboembolism Patients

Abstract: Background:The objective of the study was to describe the healthcare resource utilization (HCRU) and associated costs with hospitalized patients receiving specific versus non-specific oral anticoagulation reversal therapy for life-threatening bleeds and emergency surgeries or urgent procedures.Methods: This retrospective observational study using the Premier Healthcare Database included adult patients aged ≥ 18 years treated with idarucizumab (IDA) or 3-or 4-factor prothrombin complex concentrates (PCC) to rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In the recently published study by Spyropoulos et al, 11 patients treated with idarucizumab for the reversal of dabigatran had lower ICU admission rate, hospital cost, and shorter LOS, when compared to those treated with a non-specific, PCC-based strategy for the reversal of warfarin. As an extension of that research, the current study revealed that, the patients receiving idarucizumab also had a lower cost than those receiving using andexanet alfa for the specific reversal of DOACs rivaroxaban and apixaban, although the LOS and ICU admission rate were not statistically different among those receiving specific reversal therapies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the recently published study by Spyropoulos et al, 11 patients treated with idarucizumab for the reversal of dabigatran had lower ICU admission rate, hospital cost, and shorter LOS, when compared to those treated with a non-specific, PCC-based strategy for the reversal of warfarin. As an extension of that research, the current study revealed that, the patients receiving idarucizumab also had a lower cost than those receiving using andexanet alfa for the specific reversal of DOACs rivaroxaban and apixaban, although the LOS and ICU admission rate were not statistically different among those receiving specific reversal therapies.…”
Section: Discussionmentioning
confidence: 96%
“…Patients’ health status and risks were captured during the index hospitalization using 3M™ All Patient Refined Diagnosis Related Groups (APR-DRG) Severity of Illness and Risk of Mortality scales, 13 Deyo-Charlson Comorbidity Index (CCI) score, 14 , 15 HAS-BLED (Hypertension, Abnormal Renal/Liver Function, Stroke, Bleeding History or Predisposition, Labile International Normalized Ratio, Elderly, Drugs/Alcohol) score, 16 , 17 CHA 2 DS 2 -VASc schema (Congestive heart failure, Hypertension, Age ≥75 Years, Diabetes mellitus, prior Stroke or transient ischemic attack (TIA), Vascular disease, Age 65–74 years, Sex category) score. 16 , 18 Same set of individual comorbidities as in Spyropoulos et al (2022) 11 were also examined in this study during the index hospitalization, which included bleeds (GIB, ICH), cardiovascular diseases (Coronary Artery Disease (CAD), congestive heart failure (CHF), myocardial infarction (MI), peripheral artery disease (PAD), ischemic stroke/transient ischemic attack (TIA)), renal diseases ;(Chronic Kidney Disease (CKD), Acute Kidney Failure), cardiac procedures (coronary artery bypass grafting (CABG), other open-heart surgery, percutaneous coronary intervention (PCI), other closed cardiac procedures), and other chronic conditions (hypertension, dyslipidemia, cirrhosis/hepatitis, diabetes mellitus, chronic obstructive pulmonary disease (COPD), history of cancer, history of falls, dementia, and depression/anxiety.…”
Section: Materials/methodsmentioning
confidence: 99%
See 1 more Smart Citation